A relação fraterna e seus aspectos normativos e transgressores : uma investigação psicanalítica a partir da mitologia grega - Milharesi, Nayara Caroline (2014)
The fraternal relationship, besides taking part into an individual1s formation, makes an emotional experience possible to its members, having for each part of this relationship a different representation, as well as the development of unique individualities, even though having the same upbringing in their parent's view. Furthermore, the Greek mythology reveals, by its tragic constructions, aspects of the human psychism, which contribute with the psychoanalytical thinking, as the tragedy`s hero course swings between the normative and the transgressive space within his own path. This paper, which embraces the psychoanalytical method and refers to the dual fraternal relationship, developing in its own dynamic an antagonistic view, aims to understand within this antagonism if is it possible to identify which brother has in his psychism the predominance of the normative aspects and which has the predominance of the transgressive aspect. This paper employs the Greek mythology and the psychoanalysis, aiming to a path that resembles concepts as a fraternal function and the fraternal complex, building an approach between this two parts, so it can undergo some elements, such as rivalry and competition, envy and jealousy, the good relationship and narcissistic aspects bound to this brotherhood. Finally, it also presents analyses built under intra and intersubjective paths, being based on Greek tragedies, such as Antigone, by Sophocles (n.d./2005), Seven against Thebes, by Aeschylus (n.d./2007) and Euripides' (n.d./2005) The Phoenician Women as a resource to think about the issues around the fraternal relationship.